THE ATTITUDE OF LITHUANIAN SCHOOL STUDENTS ( YOUNG BOYS AND TEENAGERS ) TOWARDS PHYSICAL ACTIVITY AS A VALUE TO STAY HEALTHY - Ivaskiene, Vida; Minkevicius, Rimantas; Skyriene, Valentina; Smirnovas, Kestutis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Goal of the study: identifying the attitude of students (young boys and teenagers) towards physical activity as a value to stay healthy, based on their age and place of residence. The scope of the study consisted of 99 seventh-grade students (45 of them originating from rural areas, 54 from towns and cities) and 96 tenth-grade students (44 of them originating from rural areas, 52 from towns and cities), a total of 195 school students, all of them young boys and teenagers from county N. The survey was conducted using a questionnaire constructed on a basis of questionnaire forms by I.J.Zuoziene (1998) and O.Batutis (2003). Conclusion. Regardless of their age and place of residence, Lithuanian school students (boys and teenagers) consider physical activity a value to stay healthy.